Finite element method applied to modeling crosstalk problems on printed circuit boards - Khan, R.L.; Costache, G.I. (IEEE transactions on electromagnetic compatibility, 1989)
In modeling crosstalk on printed circuit boards, the distributed parameter transmission line model is applied to include the effects of electromagnetic coupling between tracks. Starting with a finite element approach, a computer model for predicting crosstalk voltages and currents in a general n+1 multiconductor configuration is outlined. After the currents on each track are calculated by using the finite element method and modal analysis, a simple radiation model is used to calculate the radiated field produced by the printed circuit boards for a frequency range of 30-1000 MHz. The algorithm presented was implemented in a series of Fortran programs, and the results obtained using this procedure compare very well with available theoretical and experimental data.< >